Komunikasi Antarpribadi Antara Orang Tua dan Anak yang Mengalami Kehamilann Tidak di Inginkan - Moch Faishal Anshori; Yulianti (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. In 2 15 marriages due to pregnancy outside of wedlock (unwanted pregnancy) increased to 8 cases, the urge to have premarital sex can be influenced by relationships and can be caused by parents, in this case Broken Home or from problems in the family itself, openness is one of the reasons. an important aspect of realizing effective interpersonal communication from a humanistic point of view. Seeing the problems above, this study focuses on interpersonal communication between parents and children who experience unwanted pregnancies. This study aims to determine 1) the openness of children who have unwanted pregnancies; 2) encouragement of parents to their child who experiences unwanted pregnancy 3) unwanted pregnancy can occur. The research method chosen by the researcher in order to conduct research on interpersonal communication between parents and children is a qualitative research method with a case study approach. Through data collection techniques such as interviews, observation, and literature study. Interviews were conducted with 3 key informants who have different family backgrounds, the results of this study lead to open communication in children having 4 aspects, namely aspects of cliché, aspects of opinion, aspects of feelings, and aspects of facts. Parental support for the child is a good solution to solve this problem so that in the end the parents of each source can re-accept, and free dating styles as a trigger for unwanted pregnancies, for some informants the condition of the family is quite influencing, as well as the lifestyle. and an increasingly open mindset that considers that sexual intercourse before marriage is normal for young people and there is a sense of